Mapping of Landslide Potential Zone with Frequency Ratio Method and Mitigation Efforts in Banjarnegara Regency, Central Java, Indonesia - Ilham Muhammad; Imsak Aditya Respati Priyono; Oktaviani Rahmania; Muhammad Rizki Maulana; Boy Marluga Silitonga; Mochamad Rafi Taufiqurrahman (Syntax Corporation Indonesia, 2022)
Indonesia is a country with a very high potential for disaster. This is supported by the existence of Indonesia which is surrounded by three world plates, namely the Eurasian plate, the Indian-Australian plate and the Pacific plate. One of natural disaster which occur in Indonesia is landslide. This situation has similarities with the research area located in the Banjarnegara Regency, Central Java. Aim of this research is to provide information on the level of influence of the class and conditioning factors of landslides, and a picture of areas that have vulnerability to landslides and as an effort to provide information to related parties. This research was conducted by geological mapping and remote sensing using DEM (Digital Elevation Model) and landsat-8 as field support data and visualization of the condition of the research area. The results of this study found that the results of mapping with frequency ratio method, the percentage of low insecurity is 66.83%, moderate insecurity is 17.94%, high insecurity is 1.87%, and very high insecurity is 0.02%. Areas with very high land movement potential are in karangkobar and pandanarum districts with a total area of 0.094589 km². The area has a very high potential because it has litology with volcanic rock types, very low vegetation and the presence of straightness. Therefore, various mitigations are needed both structural and non-structural.